2016
DOI: 10.3109/07388551.2016.1163322
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of enzymatic hydrolysis for production and functionalization of nanocelluloses

Abstract: Nanocellulose (NC) from cellulosic biomass has recently gained attention owing to their biodegradable nature, low density, high mechanical properties, economic value and renewability. They still suffer, however, some drawbacks. The challenges are the exploration of raw materials, scaling, recovery of chemicals utilized for the production or functionalization and most important is toxic behavior that hinders them from implementing in medical/pharmaceutical field. This review emphasizes the structural behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 117 publications
0
47
0
1
Order By: Relevance
“…However, the reduction of these costs has attracted the interest of research centers and companies in recent years, due to the high potential of high saccharification efficiency and high penetration, as well as the low level of pollution. With the use of enzymatic hydrolysis, high yields and almost pure cellulose material are favored, in addition to, reducing environmental impact and obtaining products suitable for biomedical applications [61].…”
Section: Nanocellulose Production Route Via Enzymatic Hydrolysismentioning
confidence: 99%
“…However, the reduction of these costs has attracted the interest of research centers and companies in recent years, due to the high potential of high saccharification efficiency and high penetration, as well as the low level of pollution. With the use of enzymatic hydrolysis, high yields and almost pure cellulose material are favored, in addition to, reducing environmental impact and obtaining products suitable for biomedical applications [61].…”
Section: Nanocellulose Production Route Via Enzymatic Hydrolysismentioning
confidence: 99%
“…). Recently, Karim and coauthors have shown the possible bonding of cellulosic monomers using 1,4‐ β‐D ‐glycosidic bonds and inter‐ and intra‐hydrogen bonds .…”
Section: Bonding Within Cellulose Bundles and Hydrolysismentioning
confidence: 99%
“…Various biomass sources have been used for the production of nanocellulose worldwide, depending on the availability of biomass in the area. The primary used natural biomass for the production of nanocelluloses is wood , . Other non‐food materials sources like jute, coir, sisal, ramie, flax, hemp, abaca, cotton, and cotton linters were also reported .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations